Elective surgery should be considered after successful conservative treatment of recurrent diverticular abscesses. (2nd April 2020) - Sigurdardottir, J.; Chabok, A.; Thorisson, A.; Smedh, K.; Nikberg, M.
Abstract: Purpose: The purpose of this study was to evaluate the disease pattern and treatment of diverticular abscesses. Methods: Patients treated for diverticulitis (K57) in Västmanland, Sweden were identified for this retrospective population-based study between January 2010 and December 2014. Patients with diverticular abscesses were included. The clinical and radiological data were extracted, and the computed tomography scans were reevaluated. Results: Of the 75 patients (45 women) with a median age of 62 years (range: 23–88 years), abscesses were localized pericolic in 42 patients (59%) and in the pelvis in 33 patients (41%). The median abscess size was 4.8 cm (range: 1.1–11.0 cm). Six patients (8%) required urgent surgical intervention during the index admission. The median follow-up time was 58 months (range: 0–95 months). During follow-up, 40 patients (58%) had disease recurrence and 35 of these patients (88%) presented with complicated diverticulitis. The median time until re-admission was 2 months (range: 3 days–94 months). Patients with pelvic abscesses developed fistulas more frequently, 3 versus 11 patients ( p  = .003). Twenty-three percent of patients with pericolic abscesses required surgery compared with 40% of patients with pelvic abscesses ( p  = .09). No patients had a recurrence of abscesses after a colonic resection. Conclusion: The majority of patients with diverticular abscesses had recurrences with repeated admissions regardless of abscess location. An unexpectedly high proportion of patients required surgical intervention during the follow-up period. A liberal approach regarding elective surgery for patients with recurrent diverticulitis abscesses who tolerate surgery seems justified.